THE CORRELATION BETWEEN LEARNING MEDIA USAGE AND INTEREST TOWARD ENGLISH ACHIEVEMENT OF THE SECOND YEAR STUDENTS OF SMPN 1 GROGOL : Learning Media Usage, Interest, English Achievement - Fachrudin Bastomi (Jurnal Penelitian Multidisiplin, 2022)
In learning English there are many factors that influence English Achievement, one of them is by using learning media and interest of the student in learning process. Both of that factors are very important to train the student to achieve the capability of knowledge that delivered. As well, the learning media usage as the complement tool that make the student have attention along with concerning to keep focus on the English material. This research have aims to know whether there is any significant correlation between the learning media usage and English achievement of the second year students SMPN 1 Gogol and whether there is any significant correlation between the interest and English achievement of the second year students SMPN 1 Grogol. The research used descriptive quantitative method a research design. Quantitative was related to the computation of number. The result of the learning media usage belongs to moderate category. First, it is proven that the 87 students get moderate score of questionnaire with the percentage is 49%. Second, for interest there are 87 students belongs to very good category with the percentage is 49%. And the last for English achievement there are 87 students belongs to good category with the percentage 49%. Finally, to correlate between two variables of data those are learning media and English achievement, later interest and English achievement the reaserach used the product moment correlation technique. From the result product moment correlation, it found out that the value of “r” is 0,181. It mean that there is positive and significant correlation between learning media usage and English achievement. And also there is positive correlation between interest and English achievement of the second year students of SMPN 1 Grogol. The result is strengthened by the result of SPSS that significant two detailed. It strengthened by the number of significant (2-tailed) 0.000. it means that the accuracy of H0 is rejection 100% right.